Pendekatan Hermeneutik Dalam Hadis-Hadis Tentang Wali Nikah - Marhumah, Ema (Musawa Jurnal Studi Gender dan Islam, 2007)
This article examines a number of Prophetic traditions Ouulits) dealing with wali (guardianship) in the context of marriage contract ('aqdun nikah) using a hermeneutical approoch. There are many approoches and assumptions with regard to studying the issue of wali. The author argues that it is necessary to link the study of waliwith that of Arabian culture. Having studied the discourse of wali mentioned in a number of hadits, as well as put them in the contexts of Islamic massage and Arabian culture, the writer concludes that the hadits dealing with wali have indeed a temporal function, and addressed to minors (children not reaching their adulthood) and those who lack capability to take care and manage their own lives. Thus the author suggests that patriarchal culture which discriminate adult, intelligent women to act as waliin the event of marriage slwuld be reviewed in order to create egalitarian society.